(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
National identity reflects of a nation’s political stance, often interwoven into its architecture. Amid Indonesia, political evolution, a profound transformation in architectural identity is occurring. Nusantara architecture has become an identity politics under President Joko Widodo’s administration, with the agenda of moving the national capital from Jakarta to the Nusantara in Kalimantan. This study aims to explore aspects of Indonesian architectural identity expressed in the design concept of the new parliament. Utilizing a descriptive qualitative approach, insights from literature and participation in webinars showcasing the winning designs from legislative competition are synthesized. Three dimensions elucidate Indonesia’s architectural identity formation within this context: symbolic representation, building and environmental aspects, and functional programming. Symbolically, the legislature’s role as the voice of the people’s existence is showcased through a monumental axis arrangement. The accommodation of the people’s existence is ensured by providing access to the legislative complex. Local identity enriches the formation of the national identity through the application of local architectural language. Furthermore, site-specific considerations play a vital role in shaping the building characteristics. Architecture, politics, and national identity encapsulating the aspirations and ideologies of a nation, reflecting in its built environment.